1997
DOI: 10.1111/j.1651-2227.1997.tb18358.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: developmental disturbance of brain and mind?

Abstract: Schizophrenia is the most severe of the mental illnesses and affects approximately 0.8% of the population in Western societies. Postmortem and neuroimaging studies show that patients with schizophrenia have slightly larger cerebral ventricles than normal and a decrease in cortical volume, most markedly in the left temporal lobe. These changes are present at diagnosis and appear to show little change over extended periods of follow‐up. Associated findings such as lack of normal cerebral asymmetry and cytoarchit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…58 Other results have shown abnormalities in the temporal lobe and limbic regions, particularly in the left cerebral hemisphere. 58,59 The results of functional brain imaging studies have supported theories of frontal lobe dysfunction, with evidence of reduced metabolic functioning in anterior brain regions. 60 Neuropathological studies have shown a wide array of findings, including a disruption of neuromigration, reflecting abnormalities in fetal brain development.…”
Section: Neuroimaging and Neuropathological Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…58 Other results have shown abnormalities in the temporal lobe and limbic regions, particularly in the left cerebral hemisphere. 58,59 The results of functional brain imaging studies have supported theories of frontal lobe dysfunction, with evidence of reduced metabolic functioning in anterior brain regions. 60 Neuropathological studies have shown a wide array of findings, including a disruption of neuromigration, reflecting abnormalities in fetal brain development.…”
Section: Neuroimaging and Neuropathological Studiesmentioning
confidence: 85%
“…Neuroimaging in schizophrenia has also shown a reversal of the normal pattern of cerebral asymmetries57 and abnormalities of the corpus callosum 58. Other results have shown abnormalities in the temporal lobe and limbic regions, particularly in the left cerebral hemisphere 58,59. The results of functional brain imaging studies have supported theories of frontal lobe dysfunction, with evidence of reduced metabolic functioning in anterior brain regions 60.…”
Section: Neuroimaging and Neuropathological Studiesmentioning
confidence: 92%
“…Furthermore, the relationship between certain viruses and schizophrenia should not be ruled out, even if neither serological evidence nor virus genome was detected in parallel with the course of the illness itself. It is hypothesized in neurodevelopmental theory in relation to maternal infection by influenza during pregnancy [32][33][34] that compromised neural development in the fetus may contribute to the liability to schizophrenia in later life. In this mechanism, neither serological nor genomic evidence is theoretically expected, since direct infection of the host's (fetus's) CNS does not necessarily occur.…”
Section: Discussionmentioning
confidence: 99%
“…The view of schizophrenia as a neurodevelopmental disorder [83][84][85] is a revival of the ideas already present in the era of high-risk research, i.e. longitudinal follow-up studies of offspring of patients with schizophrenia [83,86,87] .…”
Section: Biological Considerationsmentioning
confidence: 99%